Impact of colistin plasma levels on the clinical outcome of patients with infections caused by extremely drug-resistant Pseudomonas aeruginosa. Issue 1 (December 2017) - Sorlí, Luisa; Luque, Sonia; Segura, Concepción; Campillo, Nuria; Montero, Milagro; Esteve, Erika; Herrera, Sabina; Benito, Natividad; Alvarez-Lerma, Francisco; Grau, Santiago; Horcajada, Juan
Abstract Background Colistin has a narrow therapeutic window with nephrotoxicity being the major dose-limiting adverse effect. Currently, the optimal doses and therapeutic plasma levels are unknown. Methods Prospective observational cohort study, including patients infected by colistin-susceptibleP. aeruginosa treated with intravenous colistimethate sodium (CMS). Clinical data and colistin plasma levels at steady-state (Css ) were recorded. The primary and secondary end points were clinical cure and 30-day all-cause mortality. Results Ninety-one patients were included. Clinical cure was observed in 72 (79%) patients. The mean (SD) Css was 1.49 (1.4) mg/L and 2.42 (1.5) mg/L (p = 0.01) in patients who achieved clinical cure and those who not, respectively. Independent risk factors for clinical failure were male sex (OR 5.88; 95% CI 1.09–31.63), APACHE II score (OR 1.15; 95% CI 1.03–1.27) and nephrotoxicity at the EOT (OR 9.13; 95% CI 95% 2.06–40.5). The 30-day mortality rate was 30.8%. Risk factors for 30-day mortality included the APACHE II score (OR 1.98; 95% CI 1–1.20), the McCabe score (OR 2.49; 95% CI 1.14–5.43) and the presence of nephrotoxicity at the end of treatment (EOT) (OR 3.8; 95% CI 1.26–11.47). Conclusion In this series of patients with infections caused by XDRP. aeruginosa infections, Css is not observed to be related to clinical outcome.